Strategic Stability in the 21st Century: An Introduction - Ulrich Kühn (Journal for Peace and Nuclear Disarmament, 2023)
ABSTRACTThe concept of strategic stability has come under immense pressure in recent years. It is not only conceptually fuzzy but nuclear multipolarity, novel technologies, an exacerbating crisis in arms control, and a growing acceptance of “softer” norms are all taking a toll. At the same time, nuclear weapon states are concerned with possible instability to a degree not seen since the most severe crises of the Cold War. This special issue seeks to clarify some of the profound challenges to strategic stability while also offering novel scholarly as well as policy-relevant approaches to better understanding and mitigating the risks of instability. The three articles and one commentary focus on the US-Russian dyad and pragmatic efforts to clarify the goals and means of strategic stability between Moscow and Washington; the impact of emerging technologies in Russia’s war against Ukraine; US and Russian leaders’ perceptions of artificial intelligence as a novel and threatening capability of competition; and possible US efforts to initiate an arms control dialogue with China by early discussions on crisis management.